Integration-deficient lentivectors: an effective strategy to purify and differentiate human embryonic stem cell-derived hepatic progenitors - Yang, Guanghua (BioMed Central, 2013)
BACKGROUND: Human pluripotent stem cells (hPSCs) hold great promise for applications in regenerative medicine. However, the safety of cell therapy using differentiated hPSC derivatives must be improved through methods that will permit the transplantation of homogenous populations of a specific cell type. To date, purification of progenitors and mature cells generated from either embryonic or induced pluripotent stem cells remains challenging with use of conventional methods. RESULTS: We used lentivectors encoding green fluorescent protein (GFP) driven by the liver-specific apoliprotein A-II (APOA-II) promoter to purify human hepatic progenitors. We evaluated both integrating and integration-defective lentivectors in combination with an HIV integrase inhibitor. A human embryonic stem cell line was differentiated into hepatic progenitors using a chemically defined protocol. Subsequently, cells were transduced and sorted at day 16 of differentiation to obtain a cell population enriched in hepatic progenitor cells. After sorting, more than 99% of these APOA-II-GFP-positive cells expressed hepatoblast markers such as α-fetoprotein and cytokeratin 19. When further cultured for 16 days, these cells underwent differentiation into more mature cells and exhibited hepatocyte properties such as albumin secretion. Moreover, they were devoid of vector DNA integration. CONCLUSIONS: We have developed an effective strategy to purify human hepatic cells from cultures of differentiating hPSCs, producing a novel tool that could be used not only for cell therapy but also for in vitro applications such as drug screening. The present strategy should also be suitable for the purification of a broad range of cell types derived from either pluripotent or adult stem cells.